Correlation between serum levels of IL-15 and IL-17 in patients with idiopathic inflammatory myopathies. (May 2015) - Notarnicola, A; Lapadula, G; Natuzzi, D; Lundberg, IE; Iannone, F
<x xml:space="preserve">Abstract</x> Objectives: To assess the serum levels of interleukin (IL)-15 and IL-17 in patients with idiopathic inflammatory myopathies (IIM) and correlate them with levels of IL-1 receptor antagonist (IL-1ra), IL-6, IL-10, interferon (IFN)-γ, monocyte chemoattractant protein (MCP)-1, macrophage inflammatory protein (MIP)-1α, and MIP-1β. Possible correlations with disease activity parameters were also evaluated. Method: Sera from 14 patients with new-onset polymyositis (PM), 10 with dermatomyositis (DM), seven with anti-synthetase syndrome (ASS) and 19 healthy controls (HC) were analysed by multiplex immunoassay. Sera from 19 patients were analysed after a median follow-up of 5 months. All patients underwent physical examination, manual muscle testing (MMT) using the five-point MMT scales, the Health Assessment Questionnaire (HAQ), and serum creatine kinase (CK) measurement. All patients received glucocorticoids, and 13 were taking immunosuppressive therapy. Results: At baseline, serum levels of IL-15, IL-17, MCP-1, and MIP-1β were significantly higher in IIM patients than in HC. IL-17 serum levels were directly correlated (r = 0.39, p = 0.02) with disease duration while a significant inverse correlation was detected between IL-17 levels and MMT scores (r = –0.4, p = 0.02). The highest IL-15 levels were present in DM patients (p = 0.02 vs. PM). The most striking finding was the strong correlation between IL-15 and IL-17 levels (r = 0.60, p = 0.0001), and this correlation was even stronger in DM patients (r = 0.82, p = 0.006). Conclusions: The strong correlation between IL-15 and IL-17 in IIM patients, and especially in DM, suggests that there may be an interplay between the two cytokines in the pathogenesis of myositis. Further studies of larger patient cohorts and of muscle biopsies are needed to confirm these preliminary data.